2015
DOI: 10.1007/s00253-015-6770-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of anaerobic green fluorescent protein versus green fluorescent protein as reporter in lactic acid bacteria

Abstract: Lactic acid bacteria (LAB) are commonly used in the production of fermented and probiotic foods. Development of molecular tools to discriminate the strains of interest from the endogenous microbiota in complex environments like food or gut is of high interest. Green fluorescent protein (GFP)-like chromophores strictly requires molecular oxygen for maturation of fluorescence, which restrict the study of microorganisms in low-oxygen environments. In this work, we have developed a noninvasive cyan-green fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Anaerobic GFP (AnGFP) was developed to overcome this challenge and is capable of producing fluorescence in both aerobic and anaerobic environments (Drepper et al, 2007). AnGFP has been used to study microbes in the human gut (Landete et al, 2014) and lactic acid producing bacteria (Landete et al, 2015). Another reporter system used in anaerobic systems is the proprietary SNAP-tag™ system, which uses a modified protein derived from human DNA to tag a protein.…”
Section: Mapping Substrate Utilizationmentioning
confidence: 99%
“…Anaerobic GFP (AnGFP) was developed to overcome this challenge and is capable of producing fluorescence in both aerobic and anaerobic environments (Drepper et al, 2007). AnGFP has been used to study microbes in the human gut (Landete et al, 2014) and lactic acid producing bacteria (Landete et al, 2015). Another reporter system used in anaerobic systems is the proprietary SNAP-tag™ system, which uses a modified protein derived from human DNA to tag a protein.…”
Section: Mapping Substrate Utilizationmentioning
confidence: 99%
“…The increase in MalS fluorescence intensity may be linked with proper folding of the GFP or its maturation. GFP maturation requires molecular oxygen 25 . Interestingly, in Bacillus megaterium spores previous experimental work has shown that heat activation increases the respiration rate and thereby likely promotes the occurrence of higher molecular oxygen levels in spores 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The GFP reporter was found to be more favorable in the bacteriocinproducing backgrounds than either the RFP or the Lux system. Interestingly, a very recent study has reported the development of an optimized GFP variant suitable for anaerobic environments (39); the strains expressing GFP in the current study were analyzed under microaerobic conditions to facilitate fluorescence detection. Both the RFP and Lux systems were also investigated due to their usefulness in live tissues.…”
Section: Discussionmentioning
confidence: 99%